PENGARUH MUTASI DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SMP NEGERI 8 KOTA PROBOLINGGO - jurnalmap map; Rudito ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study was to determine partially mutations and organizational culture on the performance of teachers of SMP Negeri 8 Probolinggo. Secondly, to find out the simultaneous influence of mutation and organizational culture on the performance of teachers of SMP Negeri 8 Probolinggo City. This study uses a descriptive analysis method with a quantitative approach, data collection techniques using a questionnaire distributed throughout the population. The results show that mutation and organizational culture partially influence the performance of teachers of SMP Negeri 8 Probolinggo. Mutation and organizational culture simultaneously have a significant influence on the performance of SMP Negeri 8 teachers at Probolinggo and organizational culture has a dominant influence on teacher performance. Keywords: mutation, organizational culture, performance